Variation in Incoming Academic Preparation: Consequences for Minority and First-Generation Students - Salehi, Shima; Cotner, Sehoya; Ballen, Cissy J. (Frontiers in Education, 2020)
Recent efforts to promote diversity in the sciences, technology, engineering and math (STEM) disciplines include widening access to colleges and universities for capable but academically underprepared students. Equally important in these efforts is to provide students with support after acceptance, particularly in large, introductory STEM courses. We found that under-represented minority students and first-generation college attendees underperformed relative to their peers across STEM courses, and incoming preparation was the chief culprit in explaining these academic performance gaps, even after controlling for social psychological factors. We conclude that institutions should reconsider how they provision underprepared students with opportunities to excel in STEM. To address the variation in incoming academic preparation among students, we advocate for institutional resources supporting supplemental instruction, bridge programs, and evidence-based teaching practices.